LA EXTRA TAXATION OF THE NEW SIMPLIFIED CONFIDENCE REGIME - Ojeda Pérez, Fabián (UNIVERSIDAD DE SONORA, 2023)
Income tax plays an important role within the Mexican tax system, as it is the tax that collects the most in Mexico’s tax revenues. However, this tax has also been used as an instrument to boost certain economic sectors of the country. In this way, the present study analyzes the Simplified Regime of Trust of natural persons in the light of the extrataxation of taxes, in order to explore the characteristics of their tax treatment and explain why it is an extra-fiscal regime. It is a documentary research of a legal nature, which reviews the legal source of the scheme and the main literature on extrataxation. Among the main results, the Simplified Confidence Regime is described as extra-fiscal since it is aimed at encouraging individuals to comply with their tax obligations. Keywords: simplified confidence regime, extrataxation, compliance with tax obligations.